A multi-objective genetic algorithm approach for adaptive PSS and TCSC-based controller design. (29th March 2010) - Panda, Sidhartha; Patidar, Narayana Prasad; Singh, Rishi Kumar
This paper presents a multi-objective evolutionary algorithm approach for adaptive design of a power system stabiliser (PSS) and a thyristor controlled series compensator (TCSC)-based controller. The design objective is minimisation of both angle and voltage time trajectory deviations with respect to a post-contingency equilibrium point for a power system installed with a PSS and a TCSC controller. The optimal controller parameters of proposed controllers are coordinately designed. To show the adaptive capabilities of proposed approach, simulation results are presented at various loading conditions with parameter variations. Also, the results are compared with single objective GA approach to show the superiority of the proposed approach.